2019
DOI: 10.1039/c9ra06010c
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of surface-treated dental implant materials in contact with mammalian host and bacterial cells: titanium versus zirconia

Abstract: Early-colonizing oral bacterial adhesion and mammal cell proliferation were similar on surface-treated titanium and zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Another in vivo study also demonstrated that during experimental plaque accumulation, the total number of bacteria around the Ti implants and the counts of Tannerella forsythia (T. forsythia) and Prevotella intermedia (P. intermedia) were higher than in the zirconia implants and produced a stronger inflammatory response ( Clever et al, 2019 ). However, some studies have come to a different conclusion, for example, when Siddiqui et al evaluated the growth of oral early colonising bacteria and mammalian host cells on commercial pure Ti and zirconium oxide surfaces, in which they found no significant difference in the bacterial counts of Streptococcal strains adhering to commercial pure Ti and zirconium oxide surfaces after 1 or 3 days ( Siddiqui et al, 2019 ). The reasons for this variation may be as diverse as the experimental set-up, the strain, the surface treatment, etc.…”
Section: Intrinsic Antibacterial Materialsmentioning
confidence: 99%
“…Another in vivo study also demonstrated that during experimental plaque accumulation, the total number of bacteria around the Ti implants and the counts of Tannerella forsythia (T. forsythia) and Prevotella intermedia (P. intermedia) were higher than in the zirconia implants and produced a stronger inflammatory response ( Clever et al, 2019 ). However, some studies have come to a different conclusion, for example, when Siddiqui et al evaluated the growth of oral early colonising bacteria and mammalian host cells on commercial pure Ti and zirconium oxide surfaces, in which they found no significant difference in the bacterial counts of Streptococcal strains adhering to commercial pure Ti and zirconium oxide surfaces after 1 or 3 days ( Siddiqui et al, 2019 ). The reasons for this variation may be as diverse as the experimental set-up, the strain, the surface treatment, etc.…”
Section: Intrinsic Antibacterial Materialsmentioning
confidence: 99%
“…[27][28][29] Studies emphasized that there was a positive correlation between surface roughness produced in response to aging and bacterial colonization. 23,[30][31][32] To evaluate the adherent microbial count on the material surface, samples were gently rinsed with phosphate-buffered saline (PBS)…”
Section: Introductionmentioning
confidence: 99%
“…37 Cell colony numbers were counted, using digital colony counter by placing each agar plate on the illuminated pad and marking on the plate with a pen provided, the number of colony-forming units per 1 ml of the suspension (CFU/ml) was calculated to quantify the microbial adhesion. 38 For accelerated hydrothermal aging, all disc samples were placed in sterilization pouches, each disc was sealed a sterilization pouch in a steam autoclave (Clear autoclave class B, Clear. China).…”
Section: Introductionmentioning
confidence: 99%
“…However, poor osseointegration is one of the most serious drawbacks of zirconia as a biomaterial. Accordingly, many studies to overcome these problems through surface modification have been actively conducted in recent years [13][14][15].…”
Section: Introductionmentioning
confidence: 99%